“I just try my best to make them happy”: the role of intra-familial relationships of care in the integration of reunited refugee families - Baillot, Helen (Frontiers in Human Dynamics, 2023)
Migration through managed migration routes such as spousal and work visas is oftenhas been conceptualised as being a pragmatic choice driven by the needs of families rather than individuals. In contrast, studies of refugee integration post-migration to date have tended to analyse integration processes through the perspective of the individual rather than rather than through a family lens. Drawing from data collection using a social connections mapping tool methodology with recently reunited refugee families supported by a third sector integration service in the UK, in this paper the author makes a valuable contribution to addressing this theoretical gap. The author explores the ambivalent ways in which family relationships, and the care that flows between family members, influence emotional and practical aspects of refugees' integration. Empirically the inclusion of accounts from across the familypeople occupying different positions within their families, including from children, adds depth to our understanding of integration from a refugee perspective. Conceptually, the paper argues that a focus on familial relationships of care re-positions refugees not as passive recipients of care, but active and agentive subjects who offer care to others. The paper ends with a call for integration to be understood in a family way that fully encompasses the opportunities and limitations offered by familial care.